2019
DOI: 10.2196/10830
|View full text |Cite
|
Sign up to set email alerts
|

“It’s Not Just Technology, It’s People”: Constructing a Conceptual Model of Shared Health Informatics for Tracking in Chronic Illness Management

Abstract: Background For many people, tracking health indicators is central to managing a chronic illness. However, previous informatics research has largely viewed tracking as a solitary process that lacks the characteristics essential to tracking in support of chronic illness management. Objective To inform development of effective technologies that aid tracking of health indicators to support chronic illness management, this study aimed to construct a health informatics model … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 46 publications
(97 reference statements)
0
47
0
Order By: Relevance
“…From the same studies, some limits have been identified regarding the tools used: they talk about "unsuitable visualization and analytics tools" and "fragmented data scattered across multiple platforms". Vizer and colleagues similarly underline these inherent barriers to tools, and an article from Epstein even reports that some people find the commercial self-quantification tools useless [3,21].…”
Section: Barriers and Limitsmentioning
confidence: 99%
See 4 more Smart Citations
“…From the same studies, some limits have been identified regarding the tools used: they talk about "unsuitable visualization and analytics tools" and "fragmented data scattered across multiple platforms". Vizer and colleagues similarly underline these inherent barriers to tools, and an article from Epstein even reports that some people find the commercial self-quantification tools useless [3,21].…”
Section: Barriers and Limitsmentioning
confidence: 99%
“…In order to better characterize the quantified self experience users go through, some researchers have attempted to derive conceptual models. In 2019, Vizer et al have identified four main models related to the tracking process but we will ignore two of them as they focus on users who are already patients, hereby involving a specific clinical context which is out of scope for our study [3,22,23].…”
Section: Conceptual Modelsmentioning
confidence: 99%
See 3 more Smart Citations